Advertising myths : the strange half-lives of images and commodities - Cronin, Anne M., 1967- (International library of sociology., 2004)
Advertising is often portrayed negatively, as corrupting a mythically pure relationship between people and things. In Advertising Myths Anne Cronin argues that it is better understood as a 'matrix of transformation' that performs divisions in the social order and arranges classificatory regimes. Focusing on consumption controversies, Cronin contends that advertising is constituted of 'circuits of belief' that flow between practitioners, clients, regulators, consumers and academics. Controversies such as those over tobacco and alcohol advertising, she argues, distil these beliefs and a.